Molecular typing of Staphylococcus aureus isolated from bovine and poultry based on PCR-RFLP of spa gene - Khoramian, B; Razmyar, Jamshid (Journal of the Hellenic Veterinary Medical Society, 2023)
Staphylococcus aureus (S. aureus) is considered one of the most important pathogen in bovine and poultry. The aim of the present study was molecular typing of S. aureus strains isolated from bovine mastitis and poultry by PCR-RFLP of spa gene. Fifty eight isolates of staphylococcus aureus were obtained from bovine mastitis (n=30) and poultry (n=28). Isolation identification were done based on conventional methods then confirmed by PCR method. The spa typing was performed by amplification of the spa gene X region. Bsp143I enzyme have been used for digestion of the PCR products and analyzed by electrophoresis on 1.5% gel. Gel Compare II software was used in pattern analysis and isolates with ≥ 70 percent similarities were taken as different types. Dendrogram obtained by RAPD results showed that among the 58 S. aureus strains eight RAPD types were identified (A–H). RAPD type A was more common among isolates from bovine mastitis (11 of 30 samples) and the majority (90%) of bovine isolates clustered in group A, D and E. Cluster B contains most S. aureus isolates of poultry origin. Group B, C and G clustered 82.1% of poultry host isolates, only in two clusters (F and H), some isolates from both the bovine and poultry host clustered together (7/58, 12%). In conclusion, RFLP of spa gene product using Bsp143I enzyme can be applied perfectly for differentiating and typing of S. aureus isolates were recovered from bovine mastitis and poultry infections.